2011
DOI: 10.1007/s00702-011-0720-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced cross-sensitization to amphetamine is related to changes in the dopaminergic system

Abstract: Repeated stress engenders behavioral sensitization. The mesolimbic dopamine system is critically involved in drug-induced behavioral sensitization. In the present study we examined the differences between adolescent and adult rats in stress-induced behavioral sensitization to amphetamine and changes in dopamine (DA) and its metabolite levels in the mesolimbic system. Adolescent or adult rats were restrained for 2 h, once a day, for 7 days. Three days after the last exposure to stress, the animals were challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
(60 reference statements)
2
20
0
Order By: Relevance
“…Further, there was a significant positive association between the increases in cortisol and DA. These findings converge with previous studies on the relation of glucocorticoids and DA in animal models (Cruz et al, 2012), as well as experimental research with healthy human subjects (Walker et al, 2008). …”
Section: The Hpa Axis and Chrsupporting
confidence: 92%
“…Further, there was a significant positive association between the increases in cortisol and DA. These findings converge with previous studies on the relation of glucocorticoids and DA in animal models (Cruz et al, 2012), as well as experimental research with healthy human subjects (Walker et al, 2008). …”
Section: The Hpa Axis and Chrsupporting
confidence: 92%
“…It was predicted that, similar to previous studies with amphetamine, chronic stress would result in increased METH-induced locomotor activity (Antelman et al, 1980, Deroche et al, 1992, Cruz et al, 2011). Instead, rats exposed to CVS exhibited an initial reduction (i.e., first 10 minutes following administration) of the locomotor stimulating effects of METH (Figure 5).…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, a study by Cunningham et al found that rats who were given intra-accumbens treatment of certain opiates (such as morphine) later proved to be sensitized to the behavioral effects of amphetamine (Cunningham and Kelley 1992;Leyton 2007). Cross-sensitization and resulting hyper-responsivity of dopaminergic systems also occurs between drugs of abuse and natural rewards (Avena and Hoebel 2003a) and drugs of abuse and stress (at both behavioral and physiological levels) (Piazza et al 1990;Cruz et al 2011;Garcia-Keller et al 2013). This latter finding highlights the important role that stress may play in relapse, whereby stressful life events can act as powerful triggers of drug cravings and a history of stressful life events may even predispose a person to drug addiction.…”
Section: Evidence For the Incentive Sensitization Theorymentioning
confidence: 98%